Status of lifelong learning in Guayaquil, Ecuador - Delgado Rovayo, María Eugenia (2016)
In order to provide some context for the current state of lifelong learning in Guayaquil, the authorswill first present information regarding the political aspect of education and the state of education in the city. Then, the authorswill explore the concept of lifelong learning and define its principles for the purpose of this research. Lastly, the authorswill explain the partnership that exists between the Municipality of Guayaquil and a non-governmental organization, and evaluate a social program that they have initiated and sustained, which aims to promote lifelong learning among the citizens of Guayaquil.